Effect of topical use of essential oils on wound healing in humans: systematic review protocol (Research, Society and Development, 2022)
Objective: to synthesize the evidence available in the literature on the effect of topical use of essential oils on wound healing in humans. Method: the protocol of this systematic review was developed according to the PRISMA for systematic review protocols and is registered in the PROSPERO database (CRD42021269456). The search for studies will be performed in the MEDLINE databases via PubMed, LILACS, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials, Web of Science and Scopus. The manual search will occur through the references of the selected studies. Gray literature will also be searched. Two reviewers will participate in the selection of studies blindly and independently. The assessment of the risk of bias will be performed using the ROB-2.0 tools for randomized studies and ROBINS-I for non-randomized studies. The analysis of the quality of the evidence will be carried out with the instruments proposed by the Joanna Briggs Institute. The quantitative analysis of the studies included will be represented by the meta-analysis, however, if it is not feasible, the data will be presented through descriptive analysis. Final considerations: the results of this systematic review may contribute to evidence-based practice regarding the use of essential oils in wound healing.